(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
In line with European legislation, Regional Law No. 57 of 9 December 2024, entitled “Regulation of Digital Innovation in the Regional Territory and Protection of Digital Citizenship Rights”, introduces an organic regulatory framework aimed at governing the use of digital technologies while also promoting a balanced relationship between technological innovation and the protection of fundamental rights. This contribution focuses on governance models based on the ethical principles outlined in the regional legislation and on the regulation of artificial intelligence.